2022
DOI: 10.1177/13567667221113078
|View full text |Cite
|
Sign up to set email alerts
|

Extending the memorable tourism experience construct: An investigation of tourists’ memorable dark experiences

Abstract: Dark tourism is an important part of tourism at some destinations; however, little is known about the factors that influence the overall dark tourism experience. This research aims to contribute to this existing knowledge gap by improving our understanding of the nature of the dark tourism experience and its formation process. Through in-depth, semi-structured interviews with 15 tourists in the war zones of Iran, participants were asked to talk about their memorable experiences and why the experience was speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 159 publications
0
13
0
Order By: Relevance
“…Recent studies continue to extend the understanding of MTE by exploring connections with behavioral intentions such as revisit intention that increase tourist satisfaction and memorability (Guleria et al, 2024) and recommend intention (Hidayat et al, 2024). The studies on MTE are also being conducted at dark tourism sites (Hosseini et al, 2024); in golf tourism (Jeong, 2024) and hiking tourism (Wang et al, 2024) leaving large scope of exploration at pilgrimage sites.…”
Section: Attitude Towards Pilgrimagementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies continue to extend the understanding of MTE by exploring connections with behavioral intentions such as revisit intention that increase tourist satisfaction and memorability (Guleria et al, 2024) and recommend intention (Hidayat et al, 2024). The studies on MTE are also being conducted at dark tourism sites (Hosseini et al, 2024); in golf tourism (Jeong, 2024) and hiking tourism (Wang et al, 2024) leaving large scope of exploration at pilgrimage sites.…”
Section: Attitude Towards Pilgrimagementioning
confidence: 99%
“…, 2024). The studies on MTE are also being conducted at dark tourism sites (Hosseini et al. , 2024); in golf tourism (Jeong, 2024) and hiking tourism (Wang et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current research has shifted to demand, concentrating on tourists’ perceptions, experiences and evaluations (Boateng et al , 2018; Sarkar et al , 2022). Studies show that dark tourists are fundamentally drawn to death and disaster, and their experience presents many cognitive and emotional complexities (Iliev, 2021; Hosseini et al , 2022). Despite this growing body of research, little is understood about how tourists perceive, evaluate and develop their attitudes toward disaster memorials, dark tourism and the structural relationships among them.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Jiang et al showed that the facilities, services, and surroundings at red tourism sites act as environmental stimuli to trigger emotional and behavioural changes in tourists [15]. By representing the invisible past at red tourism sites and museums, tourists may obtain a reflective view of their contemporary society, consolidate their social perceptions, and experience an authentic perception of their own existence [4]. Following scientific and technological advances, many red tourism sites are now designed to stimulate an emotional response in visitors through their use of sound and spatial design.…”
Section: Environmental Perception and Positive Emotionsmentioning
confidence: 99%
“…In this respect, their essence and connotation are in consistence. Visiting these sites and monuments, tourists will have a strong sense of patriotism and national pride, especially after visiting the tourist destination, they will cherish peace more and cherish the present happy life [4].…”
Section: Introductionmentioning
confidence: 99%